Epistaxis in a Pediatric Outpatient Clinic: Could It be an Alarming Sign? - ElAlfy, Mohsen Saleh; Tantawy, Azaa Abdel Gawad; Eldin, Badr Eldin Mostafa Badr; Mekawy, Mohamed Amin; Mohammad, Yasmeen Abd elAziz; Ebeid, Fatma Soliman Elsayed (International Archives of Otorhinolaryngology, 2021)
Introduction Epistaxis is a common presentation among children.Objective To investigate the suitability of a simple tool of assessment for patients with epistaxis that could guide in subgrouping those with possible bleeding tendencies who may need further assessment.Methods Children who presented to a tertiary outpatient clinic with epistaxis of an unknown cause were recruited. They underwent thorough clinical assessment and answered the pediatric bleeding questionnaire and the epistaxis severity score. All patients underwent complete blood count as well as coagulation profile, and confirmatory diagnostic tests were performed as needed.Results Among the 30,043 patients who presented to the outpatient clinic over a year, 100 children had epistaxis, with an estimated annual frequency of 1 in 300. A total of 84% of the patients were younger than 12, and nearly half of these were younger than 6 years. Seventy-six patients had recurrent epistaxis, and 12 had systemic comorbidities. A significant higher percentage of patients presented with epistaxis in the hot months of the year. A total of 90% of the patients presented anterior bleeding, and the majority were treated with nasal compression only. Forty-three patients presented with epistaxis only; 37 of them were diagnosed as idiopathic epistaxis, and 6 had local causes. Fifty-seven patients presented with other bleeding manifestations, 47 of whom had a definite bleeding disorder and the other 10 had undiagnosed bleeding tendency. Those with other bleeding manifestations showed a higher frequency of positive family history of epistaxis; of being referred from a primary care physician; of having alarming low platelet count, and of presenting less seasonal variability. A bleeding score ≥ 2 showed significant value in suspecting an underlying systemic pathology as a cause of epistaxis.Conclusion The pediatric bleeding questionnaire is a useful and simple tool in the identification of pediatric patients who need further diagnostic testing to detect any underlying bleeding tendency.
Keywords: epistaxis; children; outpatient clinic; bleeding disorder